A Cross-cultural Validation of Adapted Questionnaire for Assessing Motivation to Learn Science. Issue 3 (2nd September 2018) - Shaakumeni, Simson N.; Csapó, Benő
Abstract : The aim of the present study was to examine the psychometric properties of a questionnaire adapted from Students' Motivation Towards Science Learning questionnaire developed by Tuan and colleagues, to assess motivation to learn science among Namibian Grade 12 students ( N = 755). The overall reliability of the scores on the 19-item questionnaire was 0.79. The reliability of the individual factors ranged from 0.66 to 0.77. The sample was split into two for exploratory and confirmatory factor analyses. Exploratory factor analysis ( N = 403) using principal components extraction with varimax rotation revealed an interpretable factor structure and the factor solution accounted for 56.1% of the total variance. The measurement model was validated by means of confirmatory factor analysis ( N = 352) and the results showed that the model had adequate statistical fit for the data, with the following fit indices: χ 2 /d.f. = 1.54, RMSEA = 0.039, SRMR = 0.047, TLI = 0.94 and CFI = 0.95. Construct validity was confirmed through the assessment of convergent and discriminant validity and both were found tenable. These findings indicate that the adapted questionnaire has adequate construct validity and reliability. Moreover, the findings suggest that the adapted questionnaire is suitable for assessing Namibian Grade 12 science students' motivation to learn science.